The fluctuation of serum testosterone and sex hormone binding globuline during summer intensive Training in elite swimmers - Sun, X.; Wang, L.; Song, W.; Wen, T. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
It has been examined that serum testosterone and SHBG are independent indexes to show the athletes' physiological situation. They may not change in parallel. It will be helpful to test athletes' SHBG while testing their testosterone to evaluate their physiological assimilation activity.